EDUKASI PENGEMBANGAN GULA AREN BAGI MASYARAKAT DI KECAMATAN JATIGEDE, SUMEDANG - Dwining Elfriede; Fransisca Wijaya (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
The creative industry development ecosystem can encourage the community to participate in building a sustainable tourism village. Jatigede District is one of the areas in Sumedang which has several tourist village areas. The area has enormous natural potential, one of which is the sap tree. The existing sap trees have the potential to produce palm sugar but have yet to be carried out optimally in both processing and packaging. The quality of the palm sugar produced still needs to improve, it melts quickly in storage. Product development can support sustainable tourism villages through creative industries. The problems experienced by partners included a need for more knowledge and skill regarding Good Manufacturing Practices (GMP) to meet the standards of Pangan Industri Rumah Tangga (P-IRT). Community development activity aims to develop village product that is quality and safe. The stages that will be carried out are to improve the knowledge of craftsmen through GMP training and counseling, packaging technology and product labeling, and business development. The result is the craftsmen have a deeper understanding of the training and simulation materials provided. There is a significant difference between the pre-test and post-test scores, where the post-test average score is greater than the pre-test average. Partners can perform sensory functions to differentiate palm sugar products with good and bad quality. Partners have also been able to design palm sugar packaging labels for the palm sugar.  ---  Ekosistem pengembangan industri kreatif mampu mendorong masyarakat turut serta dalam membangun desa wisata yang berkesinambungan. Kecamatan Jatigede merupakan salah satu daerah di Sumedang yang memiliki beberapa daerah desa wisata. Salah satu potensi alam terbesar di daerah ini yaitu pohon nira. Pohon nira yang ada saat ini berpotensi menghasilkan gula aren namun belum dilakukan secara maksimal baik dari segi pengolahan maupun dari segi pengemasan. Gula aren yang dihasilkan cepat meleleh selama penyimpanannya. Pengembangan produk gula aren ini mampu mendukung pengembangan desa wisata yang berkelanjutan melalui industri kreatif. Permasalahan yang dialami mitra yaitu minimnya pengetahuan dan keterampilan tentang Cara Pengolahan Pangan yang Baik (CPPB) untuk memenuhi standar izin edar Pangan Industri Rumah Tangga (P-IRT). Kegiatan pengabdian masyarakat ini bertujuan untuk pengembangan produk unggulan desa yang berkualitas dan aman. Adapun tahapan yang akan dilakukan yaitu meningkatkan pengetahuan dan keterampilan pengrajin melalui pelatihan dan simulasi mengenai CPPB, teknologi pengemasan dan label produk, pengembangan bisnis dan produk turunan. Indikator keberhasilan dari kegiatan ini adalah terdapat perbedaan yang signifikan antara nilai pre-test dan post-test dimana nilai rata-rata post-test lebih besar dari nilai rata-rata pre-test. Mitra mampu melakukan sensori yang berfungsi untuk membedakan produk gula aren dengan kualitas yang baik dan buruk. Mitra juga telah mampu mendesain label kemasan gula aren untuk gula aren yang diproduksi.